SOCIAL CHANGES AND MAINTAINING EFFORT OF SUKU ANAK DALAM (SAD) LANGUAGE IN JAMBI-INDONESIA (PERUBAHAN SOSIAL DAN UPAYA PEMERTAHANAN BAHASA SUKU ANAK DALAM (SAD) JAMBI-INDONESIA) - Bambang Prastio; Istiqomah Nurzafira (Universitas PGRI Sumatera Barat, 2021)
This article discusses the life of Suku Anak Dalam or usually called as SAD who live in rural area of Jambi Province, Indonesia. Transmigration program at SAD area in Merangin Regency creates multi-language areas. Transmigration and multilanguage makes SAD life experiences social change and its origin language and culture are threatened of extinction. Another factor is Industry Revolution 4.0 that has given positive impact towards SAD life. Beside that, its negative impact is that the cultural heritage which is the nation civilization can be extinct. Therefore an effort of maintaining the language needs to be done. A qualitative research was used to describe the data. Beside that, this article is also a multidisciplinary science in this case studying the social change occurs in SAD life then sociology study was employed. Meanwhile, language plan in the effort of maintaining the language is a language science study especially sociolinguistics. The research data were obtained from interview result and field observation. Social changes that occur in SAD life are residences, using communication devices, owning religion, vehicle, and fashion style. There are seven languages used in the transmigration area such as SAD language, Malay language, Indonesian language (national language), Javanese, Minangese, Sundanese, and Batak Language. The efforts for conserving the language done by the government (The Ministry of Education and Culture, Jambi Province Government, Jambi Language Center) are making the policy and SAD language dictionary but these actions are not optimal yet. Beside that, SAD also has done some actions in the effort of maintaining their language and culture. Based on the findings of this research, a special attention about SAD life is pivotal so that their language and culture do not become extinct.